Microtopography on poly-e-caprolactone and their wettability properties (Transactions on Additive Manufacturing Meets Medicine, 2023)
Biological tissues predominantly interact with the implant at the material surface, which can affect cell responses, such as attachment and proliferation of cells, due to differences in protein adsorption [1]. A wide array of modifications to the surface have been researched over the past decades, to achieve enhanced osseointegration and subsequently lead to less implant failure [2]. Microtopographies can influence cell adhesion by the means of biophysical and mechanobiological cues. The aim of this study was to investigate the effect of microtopography on the biophysical surface property of wettability. Four distinct microtopographies (inverted pyramids, grooves, pillars, and osteon-like structures) were designed as mold forms via 3D-CAD modelling. These molds, together with a negative control (no microtopography), were manufactured by the means of a two-photon-polymerization (2PP) printer (NanoOne, Upnano GmbH, Vienna, Austria). Poly-?-caprolactone (Mn 80k, Sigma Aldrich, St. Louis, USA) was hot-extruded into the molds. The water contact angle (WCA) was measured five times per microtopography with a contact angle goniometer (DSA25E, Krüss, Hamburg, Germany). The measurements of the WCA revealed that the microtopographies, compared to the negative control, lead either to no change or to an increase in the WCA (Pillars ?=0.1°±11.7°, Osteon-like ?=8.5°±11.3°, Grooves ?=12.5°±17.9°, Inverted Pyramids ?*=21.6°±11.2°, * p
Keywords: 2-Photon-Polymerisation; 3D Microstructuring